Desarrollo psicomotor y su relación con la alimentación en los niños de los CNH de Gualel - El Cisne del cantón Loja - Núñez Cabrera, Carlos Magno (2015)
The present research has the aim of determine the practices of feeding of the, infant and young child and its influence on the psychomotor development. This is a transversal, correlational, conducted with 120 children from 0 to 36 months enrolled in the program grow with our children ( CNH ) in Gualel-El Cisne Canton Loja in 2014 , to collect the information, surveys were applied to mothers or caregivers and the psychomotor development was assessed using the Denver test. From the total of all children had an early start of breastfeeding the 75 % obtained a normal test result of Denver unlike those who didn’t receive an early initiation of breastfeeding, in which the 17 % obtained an abnormal test. Children whom receiving an exclusive breastfeeding the 77% presented a normal test and 19% presented a doubtful or a risk one, unlike those that didn´t receiving exclusive breastfeeding in which the 67% had a normal test and the 28% had a doubtful or a risk.From the children who got supplementary feeding on time the 77% obtained a normal result and the 8% obtained an unusual result. Fort he children who didn´t get supplementary feeding on time the 33% obtained an unusual result in the test.It concludes that correct eating habits influence positively in the psychomotor development. . With the results obtained it is recommended to institutions working on behalf of children as is the MIES through CNH, the initiation and maintenance of appropriate feeding practices that ensure the integral development of children. Keywords: feeding practices, Psychomotor Development, Children under 3 years.